A crossover–crossback prospective study of dibutyl-phthalate exposure from mesalamine medications and semen quality in men with inflammatory bowel disease. (October 2016) - Nassan, Feiby L.; Coull, Brent A.; Skakkebaek, Niels E.; Williams, Michelle A.; Dadd, Ramace; Mínguez-Alarcón, Lidia; Krawetz, Stephen A.; Hait, Elizabeth J.; Korzenik, Joshua R.; Moss, Alan C.; Ford, Jennifer B.; Hauser, Russ
Abstract: Background: Phthalates are widely used chemicals with ubiquitous exposure. Dibutyl-phthalate (DBP), a male reproductive toxicant in animals, is understudied in humans. Some mesalamine medications used to treat inflammatory bowel disease (IBD) have DBP in their coating, whereas other mesalamine formulations do not. Objectives: Taking advantage of differences in mesalamine formulations, we investigated whether high-DBP exposure from mesalamine medications was associated with decreased semen parameters. Methods: 73 men with IBD taking mesalamine participated in a crossover-crossback prospective study. Men taking non-DBP containing mesalamine at baseline i.e., background exposure, crossed-over for four months to high-DBP mesalamine and then crossed-back for four months to their non-DBP mesalamine (B1 HB2 -arm;Background1 -High-Background2 ) and vice versa for men taking high-DBP mesalamine at baseline (H1 BH2 -arm;High1 -Background-High2 ). Men provided up to six semen samples (2: baseline, 2: crossover and 2: crossback). Results: We estimated crossover, crossback and carryover effects using linear mixed models adjusted for abstinence time, age, season and duration on high-DBP mesalamine at baseline. Semen parameters in B1 HB2 -arm (26 men, 133 samples) decreased after high-DBP mesalamine exposure (crossover versus baseline), especially motility parameters, and continued to decrease further even after crossback to non-DBP mesalamine (crossback versus crossover). The cumulative carryover effect of high-DBP (crossback versus baseline) was a decrease of % total sperm motility by 7.61(CI:− 13.1, − 2.15), % progressive sperm motility by 4.23(CI:− 8.05, − 0.4) and motile sperm count by 26.0% (CI:− 46.2%, 1.7%). However, H1 BH2 -arm (47 men, 199 samples) had no significant change during crossover or crossback. Conclusions: Men newly exposed to high-DBP mesalamine for four months had a cumulative reduction in several semen parameters, primarily sperm motility, that was more pronounced and statistically significant even after exposure ended for four months. Graphical abstract: Highlights: Mesalamine with coating containing dibutyl phthalate(DBP) impart high-DBP exposure. Men newly exposed to DBP containing mesalamine had a reduction in semen quality. The most robust effect of high-DBP exposure from mesalamine was on sperm motility. High-DBP effect on sperm motility persisted for 4 months after removing exposure.